2015
DOI: 10.5455/2394-6040.ijcmph20150206
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders among medical students of a rural teaching hospital: a cross-sectional study

Abstract: Background: Eating disorders are complex psychiatric syndromes in that can lead to significant and potentially life threatening medical and nutrition complications. Literature from India in this regard is restricted and issues such as eating attitudes and body shape dissatisfaction remain unexplored in the Indian setting. It has been argued that eating disorders are culture-bound disorders specific to western societies. Consequently, these conditions remain understudied in most non-western settings. Objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
0
21
2
2
Order By: Relevance
“…A positive correlation between body shape dissatisfaction and eating attitude was found in Indian medical students and female nursing students. 15,21 In another study on medical students a high score on BSQ (body shape questionnaire) scale was found to be a significant predictor of eating (disorder) morbidity. 29 In the US, one longitudinal study, found a strong and consistent relationship between body dissatisfaction and unhealthy weight control behaviours such as dieting, pills, laxatives in 2516 males and female adolescents.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A positive correlation between body shape dissatisfaction and eating attitude was found in Indian medical students and female nursing students. 15,21 In another study on medical students a high score on BSQ (body shape questionnaire) scale was found to be a significant predictor of eating (disorder) morbidity. 29 In the US, one longitudinal study, found a strong and consistent relationship between body dissatisfaction and unhealthy weight control behaviours such as dieting, pills, laxatives in 2516 males and female adolescents.…”
Section: Discussionmentioning
confidence: 96%
“…Comparing this results to other studies in India, which reported a prevalence of abnormal eating attitude as16.9%, 29.2%, 26.67%. [21][22][23] There was a wide variation in prevalence found in other countries, e.g. China: 4.5%, Spain: 7.8%, Singapore: 10.5%, Brazil: 13.3%, South Africa: 21.2%, US: 22-26%, Japan: 35%, Turkey: 45.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) However, there is dearth of literature available among health science students. (12) In addition, there are no studies that examined gender differences related to eating behaviors from India. Thus, the present study was aimed to assess gender differences in Body Mass Index, body weight perception, weight satisfaction, disordered eating and weight control strategies among Indian Medical and Nursing Undergraduates…”
Section: Introductionmentioning
confidence: 99%
“…[5057] Further, food restriction is culturally sanctioned in Indian culture when one is unwell, for “cleansing the bowel.”[36] However, several recent studies show an association between perception of body shape and higher scores on EAT-26. [182224] This could be explained by the ongoing rapid societal transitions in India and the increasing influence of western ideals.…”
Section: Discussionmentioning
confidence: 99%